Summertime dissolved oxygen concentration and hypoxia in the Zhejiang coastal area - Zhang, Xiangdong; Wang, Zelin; Cai, Huiwen; Chai, Xiaoping; Tang, Jingliang; Zhuo, Lifei; Jia, Haibo (Frontiers in Marine Science, 2022)
Introduction The Zhejiang coastal area is the most important fishery ground in East China Sea, located south of the Yangtze River Estuary. The previous studies on hypoxia and mechanisms mainly focused on the outer shelf and Yangtze River Estuary, and limited knowledge on the DO depletion and low DO information in this area. Methods In this study, the relationships among the DO spatial variation and depletion with nutrients, Chl-a, algal blooms, stratification were analyzed based on the investigation from July to August in 2020. Results and discussion The results showed that, the DO contents were high in the surface water (4.6–11.8 mg/L) than in the bottom water (3.0-8.4 mg/L) with an increasing trend from nearshore to offshore in the surface layer, but opposite in the bottom. The vertical profile of DO showed that low DO concentrations (≤3.0 mg/L) started from the water depth of 12 m with a depth of 45 m. The low DO area appeared in the northeast and central Zhejiang coastal areas covering an area of 6,000 km2 and 4,000 km2, respectively. Our analysis indicated that the successive algal blooms (Chl-a > 40.0 μg/L) occurred in late June and during the investigation prepared the low DO pool for the hypoxia development. Stratification, generated from upper warm, light, diluted freshwater from the Yangtze River and the deeper cold, heavy, salty Taiwan Warm Current ceased the vertical convection of DO in the surface, and accelerated the hypoxia development. The hypoxia starting time was earlier and the duration was longer in this complicated area. The rising temperature, more frequency of algal blooms by global warming would likely to make this worse. Continued interdisciplinary research are badly needed to get a better view in the future.